THE IMPLEMENTATION OF CORETAX ON CORPORATE TAXPAYER COMPLIANCE AND EFFICIENCY IN TAX REPORTING AT CV. X - Nosi Desnia; Kristiyanti, LMS; Dewi, Maya Widyana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the impact of implementing the Core Tax Administration System (Coretax) on corporate taxpayer compliance and reporting efficiency at CV. X. Coretax is a digital innovation developed by the Directorate General of Taxes (DGT) to modernize tax administration through an integrated and automated system. This research adopts a descriptive qualitative approach, using documentation techniques based on tax payment and reporting records from January to March 2025. The findings reveal that the implementation of Coretax has positively influenced the company's tax compliance. This is evidenced by timely tax reporting and payment, more accurate data validation, and a reduction in corrections by the tax authority. Furthermore, Coretax enhances tax reporting efficiency in terms of time, cost, and human resources. The automation and integration of e-billing within the system streamline the reporting process, eliminating the need for manual input of payment data. Therefore, Coretax proves to improve the company's internal tax governance while also strengthening the collaborative relationship between taxpayers and the tax authority.